Frequency of hospitalization in patients diagnosed with congenital talipes equinovarus (CTEV) - Okoński, Piotr; Misztal-Okońska, Patrycja; Okoński, Marek; Książek, Piotr; Goniewicz, Mariusz (Polish Journal of Public Health, 2016)
Introduction. Congenital talipes equinovarus (CTEV), also called clubfoot is the second after congenital dysplasia of the hip (CDH) most frequently occurring congenital limb defect. In Europe the deformity affects 1-2 newborns in 1000 live births.Aim. The aim of the study was to determine frequency of the deformity among other reasons for hospitalization, as well as depicting the profile of patients treated for clubfoot.Material and methods. Study method was the analysis of medical documentation from two Orthopaedic Wards of Prof. Antoni Gębala Children’s Hospital of Lublin. Medical records of patients treated for congenital talipes equinovarus (IDC 10-Q66.0) between 2008 and 2013 were the study material.Results. Results of the study show that in the analyzed period of time 310 children were hospitalized for clubfoot in hospotal. 39.35% (n=122) of the total number of patients were girls and 60.65% (n=188) were boys. The average age of patients was 3.69 years, (Me=1.09 years). Average age of girls was 4.17 (Me=1.35 years) and boys 3.89 (Me=0.83 years). The most numerous group consisted of infants up to 1 year (n=154; 49.68%).Conclusions. Clubfoot affects boys twice as often as girls. Moreover, in the examined hospital the average length of stay for patients with clubfoot has decreased. The research reveals that the average hospitalization length in children with congenital talipes equinovarus is systematically decreasing. The study shows that the number of patients being admitted to the Children’s Orthopedics Institute of the Hospital is increasing while the number of patients with clubfoot remains on the same level.